The new emerging market multinationals four strategies for disrupting markets and building brands - Chattopadhyay, Amitava (McGraw-Hill, 2012)
Featuring case studies from LG; HTC; Tata; Haier; Lenovo; Arcelik; and Natura; this book presents the results of an in-depth study of 39 EMNCs to reveal the innovative compete-from-below strategies and tactics fueling these companies' meteoric rise. --
Includes bibliographical references and index. - Print version record
Keywords: Branding (Marketing); Strategic planning; Stratégie de marque; Planification stratégique; branding; Commerce; Business & Economics; Marketing & Sales; Internet resources